Use Of Elements Of Drawing In Teaching Technology At School - et. al., Bazarbay Avezov, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article provides for teaching technology using individual elements of drawing and taking into account the requirements of the state standard.